Effect of CaO on Barium Zinc Tantalate (BZT) Dielectric Properties - Hidayani Jaafar (Trans-Tech Publication, 2013)
The effect of CaO on microstructure and dielectric properties of Ba (Zn1/3Ta2/3)O3 (BZT) ceramics was investigated. The addition of CaO disturbed the 1:2 ordering to 1:1 ordering structure of BZT ceramic. The average grain size significantly increased with the addition of CaO and formed a more compacted structure. The relative density increased with the addition of a small amount of CaO, but it decreased when the CaO content was increased. The dielectric constant (ɛr) value of the BZT significantly improved with the addition of the CaO for the specimens sintered at 1250°C and it could be explained by the increased of the relative density. However, for the specimens sintered at 1300°C, the dielectric constant value decreased with the addition of CaO which is attributed to the decrease of the relative density. The tan δ of the CaO doped with BZT ceramics is lower than pure BZT ceramics, and decreases as the CaO content increases. Meanwhile, for the percentage of bandwidth (%BW) it is shown that the best result is when it is doped with 0.5 mol% CaO and sintered at 1250°C. The best microwave dielectric properties obtained are ɛr =70.44, tan δ = 0.025 which occur for the 0.5 mol% doped CaO and when sintered at 1250°C/4 h.